PEMAKNAAN KATA ISLAM DALAM STATUS KEBERAGAMAAN UMAT BERAGAMA PERSPEKTIF AL-MARĀGI - Agus Rahman Setiawan (Sekolah Tinggi Agama Islam Sadra, 2021)
This article discusses the meaning of term Islam in the Qur’an and its relations to the diversity of religious people statuses. In the interpretation context, this interpretation of Islam brings many opinions, which-if it is classified into two forms of understanding, namely inclusive understanding and exclusive understanding. Inclusive understanding is considered more to fight for unity, unfortunately by its rival this understanding seems too loose, and is claimed not to heed the exclusive elements that are from the beginning in the Qur’an. Exclusive understanding at this stage can cause divisions among religious communities. Therefore in this article, I want to propose an alternative understanding, which accommodates and mediates the two previous understandings, according to al-Marāghis point of view. This research is a type of qualitative research conducted with study research (literature study), with descriptive-analysis writing methods and thematic figures. Finally in this research, I found that according to al-Marāghi, Islam in the Qur’an has two different contexts of meaning, namely Islam as Religion and Islam as Sharia.